2013
DOI: 10.1063/1.4824424
|View full text |Cite
|
Sign up to set email alerts
|

The effect of graphene on liquid-crystalline blue phases

Abstract: The stabilization of liquid-crystalline blue phases is recently attracting considerable interest because of the envisioned applications in fast optical displays and tunable photonic crystals. We report on the effect of surface-functionalized graphene nanosheets on the blue phase range of a chiral liquid crystal. Calorimetric and optical measurements, reproducible on heating and cooling, demonstrate that the resulting soft nanocomposite exhibits an increased blue phase temperature stability range for a minute c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 34 publications
3
25
0
1
Order By: Relevance
“…The present results are in agreement with recent findings in mixtures of CE8 with molybdenum sulfide nanoplatelets [9] and graphene nanosheets [10]. It has been shown that spherical quantum dots of similar surface coating stabilise mostly the macroscopically amorphous BPIII [4,5], whereas the anisotropic ones (nanoplatelets) affect mainly BPI [9,10]. The relatively large surfaces of nanoplatelets induce some ordering of liquidcrystalline molecules when cooling from the I phase, favoring the faster appearance of the more-ordered structure of BPI and reducing the stability range of BPIII and BPII.…”
Section: Resultssupporting
confidence: 95%
See 3 more Smart Citations
“…The present results are in agreement with recent findings in mixtures of CE8 with molybdenum sulfide nanoplatelets [9] and graphene nanosheets [10]. It has been shown that spherical quantum dots of similar surface coating stabilise mostly the macroscopically amorphous BPIII [4,5], whereas the anisotropic ones (nanoplatelets) affect mainly BPI [9,10]. The relatively large surfaces of nanoplatelets induce some ordering of liquidcrystalline molecules when cooling from the I phase, favoring the faster appearance of the more-ordered structure of BPI and reducing the stability range of BPIII and BPII.…”
Section: Resultssupporting
confidence: 95%
“…The cubic structure of BPI is favored by the presence of laponite NPs with respect to BPIII and BPII that appear in a narrower range with respect to pure CE8. The present results are in agreement with recent findings in mixtures of CE8 with molybdenum sulfide nanoplatelets [9] and graphene nanosheets [10]. It has been shown that spherical quantum dots of similar surface coating stabilise mostly the macroscopically amorphous BPIII [4,5], whereas the anisotropic ones (nanoplatelets) affect mainly BPI [9,10].…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…There have been developed many devices based on NLC with inserted dyes, micro-particles or nano-particles. These mixtures can be used for the study of particle's physical properties as well as in engineering to improve existing devices or to develop new ones [10][11][12][13][14][15][16][17][18][19]. The liquid crystals, mainly used in LCD's, combine the properties of crystalline structure of solid state with those of liquid phase, leading to an organized movement of inserted to CNT.…”
Section: Introductionmentioning
confidence: 99%